Indigofera Pellet Storage Time on Dry Matter Content, Organic Matter, Physical Properties and Palatability in Sheep - Aprilina, Ratu Anggista; Hernaman, Iman; Tanuwiria, U. Hidayat (Fakultas Peternakan, Universitas Padjadjaran, 2024)
One of the protein sources of feed ingredients that contain high protein is I. zollingeriana. The abundant harvest of I. zollingeriana requires attention in the storage process. As forage, I. zollingeriana has bulky properties. This causes less efficiency in storage and transportation. Compaction of feed particles is one of the feed processing technologies to improve storage and transportation efficiency. The compaction process can be done by making pellets. The purpose of this study was to observe the interaction between the level of adhesive (cassava) and the shelf life of I. zollingeriana pellets on the content of dry matter, organic matter, physical properties, and palatability. The research was carried out with a nested design. The resulting data was tested with ANOVA. Indigofera zollingeriana was sun-dried for 3 days, grounded using a hammer mill, and given 10, 20, and 30% of the cassava as an adhesive. The pellets are dried in the sun to dry and put in plastic and sacks, and then the top is sewn using a sack sewing machine and stored in the feed warehouse for 0, 4, and 8 weeks. The I. zollingeriana pellets were stored for 0, 4, and 8 weeks. The results of the analysis showed that there was no interaction (P>0.05) between the adhesive level (cassava) and the shelf life of I. zollingeriana pellets. I. zollingeriana can be made into pellets with or without adhesive. Storage for up to 8 weeks did not affect the content of dry matter, organic matter, physical properties, and palatability.Keywords : pellets of I. zollingeriana, dry matter, organic matter, physical properties, palatability